Comparative Assessments of PET and ASL MR Perfusion in the Evaluation of Early Dementia - Jain, Savyasachi; Gaikwad, Shailesh B; Charan, Bheru Dan; Gupta, Anu; Tripathy, Madhvi (Acta medica Lituanica, 2025)
Background: Overtly morbid dementing diseases have a prodromal MCI (mild cognitive impairment) phase which is crucial to recognize. Clinical scores provide an easy bedside assessment tool for holistic cognitive evaluation but fail to provide lead time. While routine biomarkers of brain atrophy are late to appear, non-contrast MRI perfusion studies like ASL may serve as a valuable alternative to 18F-FDG-PET for the recognition and classification of the degree of neurodegeneration in individuals with MCI, especially when FDG-PET is not available. Our study adds confidence as we noted brain regions where PET-ASL concordance was most robust and devised concordance with ACE-3 scores.Material and methods: We conducted a prospective study from Jan 2021 to Jan 2024. Cases were selected based on the inclusion and exclusion criteria, which have objective cognitive impairment. Healthy controls were selected. MRI and PET scans were performed in all cases. Perfusion values of arterial spine labeling, PET, and clinical examination were recorded.Results: We included 33 patients and 15 healthy controls in the study. We compared ASL and PET for all selected individuals. Our study showed that ASL can detect a hypo-perfusion region with a 91% sensitivity, 85.98% specificity, 89.8% PPV, and 87.62% NPV, with a diagnostic accuracy of 88.9%.Conclusion: ASL was a dependable replacement for the gold-standard FDG-PET. ASL may serve as a valuable alternative to 18F-FDG-PET for classifying the degree of neurodegeneration in individuals with prodromal AD, especially when FDG-PET is unavailable.